Motivational determinants of physical education grades and the intention to practice sport in the future - Rodrigues, Luísa (2019)
Self-Determination Theory (SDT) is amongst motivational frameworks the most popular and contemporary approach to human motivation, being applied in the last decades in several domains, including sport, exercise and physical education (PE). Additionally, Achievement Goal Theory (AGT) has presented evidence of how contextual factors may influence student’s behavior in this particular context. The main purpose of this study was to analyze the motivational climate created by the teacher in the classroom, students’ satisfaction of Basic Psychological Needs (BPN), and how their behavioral regulation could explain PE grades and intention to practice sports in the future. Method: A total of 618 students (290 female; 328 male) from the 6th to the 9th school level, aged between 10 and 18 years (M = 13.3; SD = 1.7) participated in this study. The following surveys were used for the proposed variables: Learning and Performance Orientations in Physical Education Classes Questionnaire (LAPOPECQ); the Basic Psychological Needs in Exercise Scale (BPNESp); and the Perceived Locus of Causality (PLOCp). Intentions to practice sport/physical activity in the future were assessed through a single item. Students’ PE grade was obtained through his/her teacher final assessment. Structural Equation Analysis was performed via AMOS 23.0. Results: After analyzing modification indices and model adjustment, the final model emerged: learning climate > BPN > autonomous motivation > intentions/PE grade. Results interpretation seems to indicate that i) the satisfaction of BPN are influenced by motivational climate (i.e., learning climate), ii) the individuals’ motivation is influenced by the satisfaction of three basic psychological needs (i.e., particularly competence), and iii) the motivational regulations have direct and significant effects with intention to practice sports outside school in the future and PE grades. Discussion & Conclusion: The main results showed that a climate oriented for learning has a positive impact on basic psychological needs satisfaction of students. However, only competence satisfaction had a significant positive relationship with students’ autonomous motivation, which in turn had a significant positive relation with PE grade, as well as for intentions for leisure-time sport/physical activity practice.